2012
DOI: 10.1007/s10447-012-9145-9
|View full text |Cite
|
Sign up to set email alerts
|

International Counseling Students in Turkey and Their Training Experiences

Abstract: This study examines the perceptions and experiences of international counseling students (ICSs) in university training programs in Turkey. A majority of participants reported they had adjusted positively, but did experience problems related to language, food, and customs. Participants largely also thought that the training in Turkey met their expectations, although some stated they desired more counseling coursework and applied experiences. More than half of the ICSs surveyed thought that they would not return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Overall the findings of this study are in line with previous research, supporting the notion that international counselling trainees face distinct challenges in practice. In particular, findings suggest that these ICTs encountered practical difficulties related to second language use, reiterating previously identified communication issues due to language barriers (Ilhan et al, 2012; Morris & Lee, 2004; Ng & Smith, 2009). The present study offers details on these problems: participants struggled with self‐expression in terms of articulacy, rapidity of responses and pronunciation and with understanding their clients’ speech, both due to purely linguistic elements (such as accents, unknown words) but also due to unfamiliarity with the subtle meanings of words embedded in the culture.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Overall the findings of this study are in line with previous research, supporting the notion that international counselling trainees face distinct challenges in practice. In particular, findings suggest that these ICTs encountered practical difficulties related to second language use, reiterating previously identified communication issues due to language barriers (Ilhan et al, 2012; Morris & Lee, 2004; Ng & Smith, 2009). The present study offers details on these problems: participants struggled with self‐expression in terms of articulacy, rapidity of responses and pronunciation and with understanding their clients’ speech, both due to purely linguistic elements (such as accents, unknown words) but also due to unfamiliarity with the subtle meanings of words embedded in the culture.…”
Section: Discussionsupporting
confidence: 80%
“…Acculturation difficulties and feelings of discrimination are experienced, both in counsellor education (Henfield, Owens, & Witherspoon, 2011; McKenzie‐Mavinga, 2005; Mittal & Wieling, 2006; Ng & Smith, 2009) and other subject areas (Chen, 1999; Church, 1982; Russell et al, 2008). Finally, both ICTs and international students face practical problems related to language proficiency and communication (Chen, 1999; Ilhan, Korkut‐Owen, Furr, & Parikh, 2012; Lewthwaite, 1997; Morris & Lee, 2004; Ng & Smith, 2009).…”
Section: Academic Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Though limited in number, and much of them have focused on psychological perspectives, some related studies have been conducted in the realm of problems experienced by the international students in Turkey. Some of these studies have examined international students' communication experiences (Apyadın-Şen, 2008), academic experiences (Kondakçı et al, 2009), acculturation (Bektas et al, 2006;Gunlar & Balci, 2010), help-seeking behaviors (Nebizade, 2004), counseling needs (Bektas, 2008;Ilhan, Korkut-Owen, Furr & Parikh, 2012), and adjustment problems (Elemo & Türküm, 2019). The findings of these studies revealed that students experience problems related to language, food, and customs, adjustment difficulties, loneliness, and psychological distress.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Studies on international counselling trainees (ICTs) focus mainly on the difficulties they face in the academic environment, such as adjusting to teaching style and theory Pattison, 2003); struggling with linguistic proficiency and communication (Ilhan, Korkut-Owen, Furr, & Parikh, 2012;Morris & Lee, 2004); and being subject to discriminatory behaviours by peers and tutors (Henfield, Owens, & Witherspoon, 2011;McKenzie-Mavinga, 2005;Mittal & Wieling, 2006). Less frequently, research moves beyond the academic setting and also explores the challenges that ICTs encounter in their clinical practice (placement), such as language barriers in self-expression and understanding clients, anxiety and low self-confidence related to meeting clients (Georgiadou, 2014;Ilhan, et al, 2012;Morris & Lee, 2004; and in some cases, discriminatory behaviours from clients (Mittal & Wieling, 2006).…”
Section: International Counselling Trainees' Experiences Of Clinical mentioning
confidence: 99%